Manajemen CSR PT. Kereta Api Indonesia (Persero) Melalui Program Marching Band Locomotive - Dewi, Salma Aura; Risdayah, Enok (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2023)
This research aims to find out in depth the corporate social responsibility management of PT. KAI (Persero) through the locomotive marching band program. This research aims to find out how to determine needs, plan implementation actions, and carry out monitoring, evaluation and social audits. The research results show that the Corporate Social Responsibility (CSR) management of PT. Kereta Api Indonesia (Persero) through the Locomotive Marching Band Program through several stages. The first stage of determining needs includes efforts to accommodate people's skills in the arts sector. The program planning stage includes the formation of the Locomotive Marching Band unit and implementing the program according to the plan. The monitoring stage focuses on monitoring the progress of the program in accordance with the established plan. Finally, the social evaluation and audit stage shows that the program is running well and providing benefits to stakeholders.